Money Politics In The Electoral Law And The Law Of Election - Yudhi Atmaja; Ira Alia Maerani (Jurnal Daulat Hukum, 2019)
This study aims to identify and analyze the rampant money politics in society. In the process of grassroots democracy, the practice of money politics thrives. Since it is considered a fairness, the public no longer sensitive to the dangers. They let him, because they do not feel that money politics normatively should be shunned. Everything went to the fair. Although clearly the case of money politics, and it was recognized by the community, but there was no protest. People consider money politics as something normal for economic reasons and partly because of their ignorance.This is due to factors Regulatory, there is no provision of law which limits Election Supervisory Agency (Bawaslu) in maximizing its role, Bawaslu not authorized to call forced the clarification process, and their obligation to prepare a minimum of two (2) evidence in forwarding recommendation, The intensity of inter-agency presence is still weak short handling time violation. Besides, some people regard it as something normal. The public will know the actual allegations of money politics and in general do not want to report because of the difficulty of proving.Keywords : Money Politics; Law; Election Supervisory Agency (Bawaslu).